Tradition of Basiacuong in Batu Belah, Kampar District, Kampar Regency - Apriyanti, Viki; Sukenti, Desi (Riviera Publishing, 2023)
Riau Malay culture is a culture with various traditions. One of them is the Basiacuong oral tradition in the bakampuong nemo event. The purpose of this research is to describe the structure, the literary genre, and the message contained in basiacuong bakampuong nemo in Batu Belah village. This research is qualitative research with a descriptive method. This research includes ethnographic research. The data analysis technique used is descriptive analysis with interviews and observations. The study results show that the first basiacuong structure is the opener. The second structure is content; this structure discusses the application and sign of application. The third structure is the closing which ends with the open cello, which means dissolving the event and going home. Furthermore, for the basiacuong genre in Bakampung Nemo, there are three types: the Traditional Expression genre with 20 data, the Parable genre with 14 data, and the Pantun genre with 8 data. Finally, the mandate contained in basiacuong bakampung nemo, namely that you should follow the example that was imposed by the link mamak and the people of the house because there is an attitude of respect and the way you look polite both in terms of answering and asking questions.